The Notion of 'Were' in Yoruba Conception of Mental Illness (Nordic Journal of African Studies, 2005)
The conception of mental illness has a narrower focus than the western view. While the notion of ‘were’ merely refers to the manifestation of mental disorder, mental illness in the west involves minor stages of mental problems. This paper attempts to examine the Yoruba concept of mental illness. It is assumed that the Yoruba view of mental illness is narrower. ‘Were’ defines mental illness from the terminal point of view. This has implications for both help seeking behaviour and social interaction. The study was carried out in Ibadan, the capital city of Oyo State of Nigeria and a Yoruba community. Data were collected from ten key informants who are traditional healers. The Yorubas classify mental illness into three categories – ‘Were Amutorinwa’, ‘Were Iran’ and ‘Were Afise’. The onset of mental illness is usually observed in the wild behaviour of patients while help seeking mostly commences at this crisis stage. Usually, mental illness has negative stigma, as ‘were’ is a derogatory concept of abuse. There is need for appropriate mental health education as regards mental health related problems, diagnosis, and prevention in order to avoid the terminal stage of ‘were’.